Demystifying the Fulbright Scholarly Experience. (December 2022) - Perreault, Gregory P.; Dimitrova, Daniela V.
Global challenges in combating a range of issues—the coronavirus pandemic, climate change, hostility, migration, misinformation—necessitate global collaboration. The Fulbright Scholar programs provide numerous ways in which to develop the tools to support such collaboration. In this commentary, we provide an overview of the Fulbright experience, reflect on Fulbright's potential for enhancing scholarship in journalism and mass communication, and pinpoint areas scholars should consider in applying for their own Fulbright grant. The Fulbright is an essential tool in addressing the global problems that plague our world, and this essay serves as an introduction to the Fulbright experience.